PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN POLITIK EKONOMI UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA BERPIKIR KOMPREHENSIF - Sudarmiani Sudarmiani (Jurnal Pendidikan, 2012)
The average of the student' achievement in Politic of Economy subject at the Economy Study program, IKIP PGRI MADIUN, which can only reach 60 (C). The main obstacle encountered by the students is that they cannot comprehensively think over proposed cases by making use of rich perspectives of some disciplines.The subject of the research are the students of semester VI, Economy Education Study Program. The research is designed under class action research with three cycles to observe the learning events and achievements by using Problem-based Learning to encourage students to think comprehensively.The result of the research show that problem-based learning technique is capable of encouraging the students to think comprehensively, as shown on students' achievement, where in cycle 1, 13 students (43%) get B, in cycle 2, 16 students (53%), and in cycle 3, 23 students (77%).The non-test achivement during the implementation of problem-based learning show a result that in cycle 1 where: 9 students (30%) give their opinions, 10 students (33.33%) ask questions, 9 students (30%) answer questions, and 9 students cooperate to solve problems. The result of cycle 2 shows that: 20 students (66.60%) give their opinions, 21 students (70%) ask questions, 20 students (66.66%) answer questions, and 19 students cooperate to solve problems. The result of cycle 3 shows that: 25 students (83.33%) give their opinions, 28 students (93.30%) ask questions, 23 students (80%) answer questions, and 24 students cooperate to solve problems.